2017
DOI: 10.1159/000479437
|View full text |Cite
|
Sign up to set email alerts
|

Different Clinical Courses on Long-Term Follow-Up of Age-Related Macular Degeneration Patients Treated with Intravitreal Anti-Vascular Endothelial Growth Factor Injections

Abstract: Purpose: To assess the long-term outcome of neovascular age-related macular degeneration (AMD) treated with multiple intravitreal anti-vascular endothelial growth factor (VEGF) injections. Methods: All patients treated with over 30 intravitreal anti-VEGF injections for neovascular AMD between 2007 and 2014 were retrospectively reviewed. Results: A total of 67 eyes received 2,960 (mean 45 ± 9.1 per eye) anti-VEGF injections. Eyes with good final visual acuity (VA) had better initial VA (p = 0.020) and maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(14 reference statements)
2
5
0
Order By: Relevance
“…VA assessment was achieved at the sixth month in a total of 23 eyes: 19 of these (82.6%) had either maintained (no change from baseline) or improved VA at the 6-month follow-up. These results are consistent with those of another clinical study (51).…”
Section: Change From Baseline C -------------------------------------supporting
confidence: 93%
“…VA assessment was achieved at the sixth month in a total of 23 eyes: 19 of these (82.6%) had either maintained (no change from baseline) or improved VA at the 6-month follow-up. These results are consistent with those of another clinical study (51).…”
Section: Change From Baseline C -------------------------------------supporting
confidence: 93%
“…A good early functional response may, however, precede the anatomic response and go along with excellent long-term functional results: Attaining a satisfying functional 3-year outcome was closer (OR 9.8) correlated to a BCVA of ≥70 compared to <70 letters than to absence or presence of lesion activity (OR 1.6) by end of the loading phase following a treat-and-extend protocol 49. This is supported by another recently published study which found that independent of the number of injections, eyes with good initial BCVA had a good functional outcome over up to 4 years whereas eyes with poor initial BCVA despite a good initial visual gain deteriorated during the follow-up which was associated to the presence of intra- and subretinal fluid and subretinal fibrosis 48. Today, virtually no retina expert would delay intravitreal treatment in nAMD until a five-letter loss of vision despite the presence of intra- or subretinal fluid.…”
Section: Discussionsupporting
confidence: 52%
“…Usually, the second eye is treated earlier resulting in a better long-term outcome 57. Several factors independent of the anti-VEGF drug in use and disease activity are related to the response to treatment, which is beyond the scope of this review 28,37,48,5660. To summarize these studies, the portion of eyes achieving a good BCVA (≥70 compared), a complete absence of any intra- and subretinal fluid by end of the first and second year of treatment and allowing a treatment extension to 12 or more weeks after 1 and 2 years may become more relevant as markers of treatment efficacy 44,49.…”
Section: Discussionmentioning
confidence: 99%
“…If macular stability is achieved, this may be maintained in a subgroup of patients for up to 8 years [ 25 , 78 ]. A baseline visual acuity of ≥ 70 ETRDS letters and an early satisfying functional response to treatment are more reliable predictors of long-term outcomes than lesion activity at the end of the loading phase [ 79 ] which may be outweighed by the presence of intra- and subretinal fluid as well as subretinal fibrosis at the end of the loading phase [ 80 ].…”
Section: Discussionmentioning
confidence: 99%